The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fonc.2022.818447
|View full text |Cite
|
Sign up to set email alerts
|

The Basis and Advances in Clinical Application of Cytomegalovirus-Specific Cytotoxic T Cell Immunotherapy for Glioblastoma Multiforme

Abstract: A high percentage of malignant gliomas are infected by human cytomegalovirus (HCMV), and the endogenous expression of HCMV genes and their products are found in these tumors. HCMV antigen expression and its implications in gliomagenesis have emerged as a promising target for adoptive cellular immunotherapy (ACT) strategies in glioblastoma multiforme (GB) patients. Since antigen-specific T cells in the tumor microenvironments lack efficient anti-tumor immune response due to the immunosuppressive nature of gliob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 193 publications
(176 reference statements)
0
15
0
5
Order By: Relevance
“…In line with these findings, a randomized phase II clinical trial found that dual treatment with nivolumab and ipilimumab is efficacious and promising for patients with metastatic sarcoma 16 . Conversely, immunopathological assays demonstrated that immunocoexpression of PD‐L1 and TIM3 is most frequent in TILs from solid tumors and that these subsets characterize the most dysfunctional or exhausted fraction of TILs 37,38 . Accordingly, we hypothesized that the TIM3 blockade will act cooperatively with CTLA‐4 and PD‐L1 blockade to elicit anti‐tumor effects.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In line with these findings, a randomized phase II clinical trial found that dual treatment with nivolumab and ipilimumab is efficacious and promising for patients with metastatic sarcoma 16 . Conversely, immunopathological assays demonstrated that immunocoexpression of PD‐L1 and TIM3 is most frequent in TILs from solid tumors and that these subsets characterize the most dysfunctional or exhausted fraction of TILs 37,38 . Accordingly, we hypothesized that the TIM3 blockade will act cooperatively with CTLA‐4 and PD‐L1 blockade to elicit anti‐tumor effects.…”
Section: Discussionmentioning
confidence: 84%
“…16 Conversely, immunopathological assays demonstrated that immunocoexpression of PD-L1 and TIM3 is most frequent in TILs from solid tumors and that these subsets characterize the most dysfunctional or exhausted fraction of TILs. 37,38 Accordingly, we hypothesized that the TIM3 blockade will act cooperatively with CTLA-4 and PD-L1 blockade to elicit anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of CAR T-cells in glioblastoma (GB) has been limited, owing to the lack of well-described tumor-specific antigens that are expressed homogenously and frequently [ 177 ]. Cell surface antigens confined to tumor cells are ideal candidates, as they avoid the toxic effects caused by CAR T-cells recognizing normal organ tissue [ 178 ].…”
Section: Car-modified Immune Cells In Solid Tumorsmentioning
confidence: 99%
“…HER2 is being studied as a potential target in a number of clinical trials (NCT03389230, NCT03423992). Moreover, to target GB-related surface proteins, some therapeutic trials have used genetically modified cytomegalovirus (CMV)-specific T-cells that express CARs [ 177 ]. In this context, Ahmed et al showed that the administration of autologous HER2-CAR-modified virus-specific T-cells (VSTs) could be correlated with clinical benefit in patients with advanced GB [ 186 ].…”
Section: Car-modified Immune Cells In Solid Tumorsmentioning
confidence: 99%
“…Існує велика кількість імунотерапевтичних способів лікування, які розділяють на специфічні та неспецифічні, активні та пасивні, клітинні та антигенні, інфекційні та молекулярно-генетичні тощо. Велику увагу приділяють вивченню можливості створення високоактивних імунотерапевтичних препаратів, які б мали високу антигенність за рахунок ад'ювантів та вірусів і здатність спричинити специфічну протипухлинну відповідь в організмі [1,2]. Варті уваги дослідження з вивчення та с творення імунотерапевтичних препаратів із інфікованих вірусами пухлин, які мають як високу антигеність, так і сильну здатність стимулювати цитотоксичну активність імунних клітин в умовах пухлинної імуносупресії [1,2].…”
Section: вступunclassified